2020
DOI: 10.1002/bdd.2229
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies prediction of pharmacokinetics and tissue distribution of doxorubicin by physiologically‐based pharmacokinetic modeling

Abstract: The aim of the study was to develop a physiologically‐based pharmacokinetic (PBPK) model to describe and predict whole‐body disposition of doxorubicin following intravenous administration. The PBPK model was established using previously published data in mice and included 10 tissue compartments: lungs, heart, brain, muscle, kidneys, pancreas, intestine, liver, spleen, adipose tissue, and plasma. Individual tissues were described by either perfusion‐limited or permeability‐limited models. All parameters were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Here, we determined the concentrations of DOX in rat plasma and six tissues following a single intravenous dose of 5 mg/kg. Consistent with previous studies [12,26], our data show that the intravenous bolus injection of DOX produces high plasma concentrations, which fall quickly due to a rapid and extensive distribution into tissues (Figure 3). More importantly, we found that short-term (≤10 d) administration of AR, whether a single-dose co-treatment or multiple-dose pre-treatment, was ineffective at changing the plasma pharmacokinetics of DOX (Table 3).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we determined the concentrations of DOX in rat plasma and six tissues following a single intravenous dose of 5 mg/kg. Consistent with previous studies [12,26], our data show that the intravenous bolus injection of DOX produces high plasma concentrations, which fall quickly due to a rapid and extensive distribution into tissues (Figure 3). More importantly, we found that short-term (≤10 d) administration of AR, whether a single-dose co-treatment or multiple-dose pre-treatment, was ineffective at changing the plasma pharmacokinetics of DOX (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…DOX administered as a conventional injection is widely distributed in the plasma and tissues but can hardly cross the blood-brain barrier [12]. There are three main metabolic routes of DOX in mammals: one-electron reduction, two-electron reduction, and deglycosylation [13].…”
Section: Introductionmentioning
confidence: 99%
“…The time from drug exposure to the epithelial effects varies for different species, doses, administration routes and type of chemotherapeutics, and partly follows species-specific differences in crypt turnover. For instance, after an intravenous dose of DOX, the concentration in the intestine is about 100 times higher than in plasma in animals and humans ( Luo et al, 2017 ; Lee et al, 2020 ). Although the DOX concentrations in the intestines might be similar as in the liver, kidney, and heart, they cause greater damage to the IECs because these cells have a rapid and extensive proliferation ( Figure 3 ) ( Luo et al, 2017 ).…”
Section: Pathophysiology Of Chemotherapeutics-induced Mucositismentioning
confidence: 99%
“…in vitro-to-in vivo extrapolation, IVIVE). On the other hand, physiologically-based PK (PBPK) modeling allows for characterizing dynamic changes in hepatic concentrations in pre-clinical species and scaling-up to humans (Lee et al, 2020) where the CL int and tissue-toplasma partition coefficient (K p ) are needed. Both IVIVE and PBPK modeling require a structural liver model (Rane et al, 1977;Houston, 1994;Hallifax et al, 2010;Miller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%